In vitro study of various factors in isolation, expansion and differentiation of mesenchymal stem cells from human umbilical cord - Salehinejad, Parvin (2012)
The Wharton’s Jelly (WJ) of the umbilical cord is a rich source of mesenchymal stem cells (MSCs) with a various potential therapeutic applications. Human umbilical cord mesenchymal stem cells (hUCMCs) can be isolated with different methods, expanded and differentiated into neuron, astrocyte and oligodendrocyte in vitro. In the first study, four methods to isolate hUCMCs were compared. Three of them were based on using an enzyme cocktail containing collagenase, hyaluronidase and trypsin (CHT), collagenase /trypsin (CT) or trypsin alone (TRP) and the other was based on the explant culture (Exp) method. In the second experiment, the competence of DMEM/ F12 and alpha-MEM/Glutamax (α-MEM/GL), also the epidermal growth factor (EGF) and fibroblast growth factor (FGF) role to expand hUCMCs were evaluated. Finally, hUCMCs were examined for their differentiation rate into neural lineage cells by six various cocktails made of a base media (DMEM/LG), 10 % FBS, retinoic acid (RA), dimethyl sulfoxide (DMSO), EGF and FGF. Comparison of the four isolation methods of the hUCMCs showed that more cells were isolated in the CT, CHT and TRP groups, respectively. Cells were successfully isolated in TRP group but they did not propagate normally. Flow cytometry analysis revealed that CD44, CD73, CD90 and CD105 were expressed on the cell surface in all groups, but there was no expression of hematopoietic lineage markers, CD34 and CD45, in any of the groups. In addition, the expression of C-kit and OCT-4 in enzymatic (CT and CHT) groups was greater than Exp group. One-way ANOVA showed that cell activity rate in the Exp group was significantly higher (P<0.001) than the other groups. A positive alkaline phosphatase activity and differentiation to adipogenic and osteogenic lineage was detected in the hUCMCs of all groups. The ratio of CD44 and CD105 expression cells were similar in DMEM/F12 and α-MEM/GL groups, while in both of the groups expression of the hematopoietic cells surface marker CD34 were negative. Differentiation potential into adipogenic and osteogenic cells were similar in both groups. Student`s t-test for evaluation of cell metabolism with WST-1 showed that the quality of the expanded cells in α-MEM/GL group was significantly higher (P<0.001) than DMEM/F12 group. Population doubling time (PDT) was calculated at 60 hours for DMEM/F12 group, while it was 47 hours in α-MEM/GL group that this difference was statistically significant (P<0.001). Data sets were compared using two- way ANOVA. Semi-quantitative RT-PCR revealed that the TERT in hUCMs/EGF was 0.26 ± 0.06. Cell cycle analysis showed that EGF has caused 37.34± 9.8% and 7.71± 0.53% of the hUCMs to move in the S and G2/M phases, respectively. While, after exposure to FGF 29.92± 2.55% and 9.92± 0.24% of the cells progressed to S and G2/M phases, respectively. Induction of neuronal differentiation with various cocktails showed that there was no statistically significant difference (one-way ANOVA with a post hoc Tukey’s test) among the groups. Despite, the cocktail consist of DMEM/LG, FBS, RA, FGF, and EGF (DF/R/Fg/E group) resulted in the expression of the highest percentage of nestin, ß-tubulin III, neurofilament, and CNPase 69.7 ± 6%, 76 ±1.7%, 89 ±9.5%, and 16.3 ±5.2%, respectively. Also, in this group and the DF/Ds/Fg/E group, the highest cell proliferation was observed. On the other hand, DF/Ds/Fg/E group had the highest percentage of GFAP expression (36 ±12.5%). While, the expression level of NF, GFAP, and CNPase was at least in the DF group. The least percentage of nestin and ß-tubulin III expression was observed in the DF/Ds group. It may be concluded that isolation technique affects both the amount and the quality of the isolated hUCMCs. When collagenase/trypsin enzymes are used for isolation of hUCMCs, the waiting time for primary culture is shorter, the number of isolated cells is higher and pluripotency properties of them were greater. The type of culture media also affects the quality of the harvested cells. α-MEM/GL supports hUCMCs growth more strongly than DMEM/F12. Furthermore, growth factors also affect the TERT expression and cell cycle phases. In this case, EGF increases TERT expression and the number of cells that progress towards S/G2/M phases. In addition, hUCMCs differentiate into various neuronal cell types successfully; the amount of different neuronal cell types is influenced by inducing agents. FGF and EGF are important inducers for differentiation of hUCMCs into neuron, astrocyte and oligodendrocyte. RA can induce hUCMCs to differentiate into neuron and oligodendrocyte; while in contribution to astrocyte differentiation, DMSO had a pivotal role. From this study, it can be concluded that different isolation methods can effect on characteristics of the mesenchymal cells from human Wharton’s Jelly. These cells are able to expand in culture with various media and growth factors and differentiate into neural cells.